Pharmacological profile of a tachykinin antagonist, spantide, as examined on rat spinal motoneurones. - Yanagisawa, M. (1990)
1. The pharmacological profile of a tachykinin antagonist, [D-Arg1, D-Trp7,9, Leu11] substance P (spantide), was studied on motoneurones of the isolated spinal cord of the newborn rat. For this purpose, potentials were recorded from a lumbar ventral root extracellularly and drugs were bath-applied in the presence of tetrodotoxin (TTX). 2. Neurokinin A (NKA), a NK2-receptor selective agonist, induced concentration-dependent depolarizations, which were antagonized by spantide. Analyses of concentration-response curves suggested a competitive type antagonism with a pA2 of 6.5. 3. Depolarizations induced by acetyl-Arg6-septide, a NK1-receptor selective agonist, were also antagonized by spantide with a pA2 of 6.5. 4. Spantide (0.5-16 microM) had no depolarizing action on the ventral root in the presence of TTX. 5. Spantide antagonized the depolarizing action of substance P (SP) when SP was applied at low concentrations (0.1-0.3 microM) or by short duration pulses in artificial cerebrospinal fluid containing TTX, but much higher concentrations of spantide (4-10 microM) were needed to exert an antagonistic action against SP than against acetyl-Arg6-septide or NKA. 6. Thyrotrophin-releasing hormone, L-glutamate, GABA, and noradrenaline, also induced depolarizations of the ventral root in the presence of TTX but the responses to these agonists were not depressed by spantide (16 microM). 7. These results suggest that there is a subtype of tachykinin receptors on neonatal rat spinal motoneurones to which NKA, acetyl-Arg6-septide and spantide bind competitively with high affinity.(ABSTRACT TRUNCATED AT 250 WORDS)